2021
DOI: 10.1002/anie.202105171
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of CO2 with a Borylnitrene: Formation of an 3‐Oxaziridinone

Abstract: The reaction of a borylnitrene with carbon dioxide is studied under cryogenic matrix isolation conditions. Photogenerated CatBN (Cat=catecholato) reacts with CO2 under formation of the cycloaddition product CatBNCO2, a 3‐oxaziridinone derivative, after photoexcitation (>550 nm). The product shows Fermi resonances between the CO stretching and ring deformation modes that cause unusual 13C and 18O isotopic shifts. A computational analysis of the 3‐oxaziridinone shows this cyclic carbamate to be less strained tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 84 publications
1
6
0
1
Order By: Relevance
“…In earlier studies on the photochemical reactivity of 1 , the a ̃ 1 A 1 state, being similar to vinylidene, was presumed to be attained after irradiation with λ > 550 nm and expected to react fast with N 2 , CO, CH 4 , CO 2 , and D 2 as shown in Scheme a. Also, computational studies showed very low barriers for the reaction of the a ̃ 1 A 1 state with D 2 and CO 2 . , In addition, experiments have shown an efficient intermolecular C–H insertion for some boryl nitrenes in the solution phase. ,, The small measured kinetic isotope effect is indicative of an insertion reaction rather than a hydrogen abstraction, radical recombination mechanism . This in turn suggests that a closed-shell singlet state is responsible for the high reactivity of boryl nitrenes toward closed-shell species.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In earlier studies on the photochemical reactivity of 1 , the a ̃ 1 A 1 state, being similar to vinylidene, was presumed to be attained after irradiation with λ > 550 nm and expected to react fast with N 2 , CO, CH 4 , CO 2 , and D 2 as shown in Scheme a. Also, computational studies showed very low barriers for the reaction of the a ̃ 1 A 1 state with D 2 and CO 2 . , In addition, experiments have shown an efficient intermolecular C–H insertion for some boryl nitrenes in the solution phase. ,, The small measured kinetic isotope effect is indicative of an insertion reaction rather than a hydrogen abstraction, radical recombination mechanism . This in turn suggests that a closed-shell singlet state is responsible for the high reactivity of boryl nitrenes toward closed-shell species.…”
Section: Introductionmentioning
confidence: 98%
“…In matrix isolation experiments, 3-nitreno-1,3,2-benzodioxaborole 1 CatBN (Cat = catecholato) is formed in situ after photolyzing the corresponding azide precursor, 2-azido-1,3,2-benzodioxaborole 2 , which is codeposited with different cryogenic matrix materials (Scheme a) . Boryl nitrene 1 , which has a triplet ground state ( X ̃ 3 A 2 ), has shown high thermal reactivity toward O 2 and high photochemical reactivity toward N 2 , CO, CH 4 , CO 2 , and D 2 when irradiated with light of wavelength λ > 550 nm under matrix isolation conditions (Scheme a). ,, An electronic structure study of 1 revealed the energetic ordering of states of 1 as X ̃ 3 A 2 < a ̃ 1 A 1 < b ̃ 1 A 2 . The closed-shell singlet state ( a ̃ 1 A 1 with leading configuration π 2 σ 0 , Scheme b) thus is the lowest singlet state, contrary to phenyl nitrene in which a ̃ 1 A 2 is significantly below the b ̃ 1 A 1 state. ,, The orbital occupancy in the a ̃ 1 A 1 state is similar to that of the highly electrophilic vinylidenes, and their reactive centers are related by an isoelectronic substitution of the CC by the BN unit (Scheme b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27,28] In contrast to I, donor atom stabilized borylnitrene, 2nitreno-1,3,2-benzodioxaborole (V) displays a triplet electronic ground state, which was confirmed by matrix isolation IR, UV/Vis, and EPR spectroscopy and by monitoring its reactivity with dinitrogen, molecular oxygen, carbon monoxide, and carbon dioxide. [29,30] In general, aryl and alkyl substituted nitrenes have triplet electronic ground states, making them highly transient species, and their detection usually requires time-resolved spectroscopy or cryogenic temperatures (VI). [31] It should be stressed that there is no report on the structure and reactivity of PN with organic molecules so far.…”
Section: Introductionmentioning
confidence: 99%
“…Die Existenz von Singulett‐Nitrenen, wie Sufinylnitren ( III ) und Thiophosphorylnitren ( IV ), wurde durch Matrixisolationsspektroskopie bestätigt (Schema 2). [27, 28] Im Gegensatz zu I weist das Donoratom‐stabilisierte Borylnitren 2‐Nitren‐1,3,2‐benzodioxaborol ( V ) einen elektronischen Triplett‐Grundzustand auf, was durch Matrixisolations‐IR‐, UV/Vis‐ und ESR‐Spektroskopie, sowie die Verfolgung seiner Reaktivität mit Distickstoff, Kohlenstoffmonoxid und Kohlenstoffdioxid, bestätigt wurde [29, 30] . Aryl‐ und alkylsubstituierte Nitrene weisen allgemein einen Triplett‐Grundzustand auf, sind dadurch sehr kurzlebig, und ihr Nachweis erfordert zeitaufgelöste Spektroskopiemethoden oder kryogene Temperaturen ( VI ) [31] …”
Section: Introductionunclassified